2008
DOI: 10.1111/j.1467-9922.2008.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency Level and the Interaction of Lexical and Morphosyntactic Information During L2 Sentence Processing

Abstract: Using a self-paced reading task, the present study explores how second language (L2) German speakers at different proficiency levels use case-marking information when processing subject-object ambiguities in German. Results indicate that advanced L2 German speakers rapidly integrated case-marking information during online processing, exhibiting a subject preference similar to German native speakers. However, there was evidence that the relative processing difficulty of object-first sentences was influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 33 publications
11
107
2
Order By: Relevance
“…Existing work on online processing in L1 English-L2 German has found that intermediate and advanced learners tend to have similar subject-first parsing strategies as native speakers (Jackson 2008(Jackson , 2010. Overall, these results seem to reflect target parsing strategies and so do not support the notion that L2 processing is generally "shallower" than native processing.…”
Section: Introductioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Existing work on online processing in L1 English-L2 German has found that intermediate and advanced learners tend to have similar subject-first parsing strategies as native speakers (Jackson 2008(Jackson , 2010. Overall, these results seem to reflect target parsing strategies and so do not support the notion that L2 processing is generally "shallower" than native processing.…”
Section: Introductioncontrasting
confidence: 58%
“…Two studies (Jackson 2008(Jackson , 2010 in particular provide interesting points of comparison with Grüter. These studies also tested the comprehension of simple tense and compound tense wh-questions, but with case-marking information unambiguously marking thematic roles.…”
Section: Processing At Higher Proficiencies In L1 English-l2 Germanmentioning
confidence: 98%
“…The L1 English participants in another self-paced reading study of case and word order in L2 German (Jackson, 2008) also showed a native-like preference for subjectfirst order, in this case with temporarily ambiguous wh-questions. The native-like preference was only evident among a higher proficiency L2 participant group and only in sentences with simple past tense, in which the lexical verb preceded the second verbal argument in the disambiguating region, and not with the present perfect, in which the lexical verb comes at the end of the sentence in German, after the disambiguating region.…”
Section: On-line Sensitivity To Case Markers In Non-native Processingmentioning
confidence: 87%
“…In a visual world eyetracking experiment, we have been testing whether inflection is processed incrementally by intermediate to advanced adult L2ers (Hopp, in preparation). A series of previous studies demonstrated that even advanced L2 learners do not seem to use case information incrementally when parsing non-canonical word orders (e.g., Hopp, 2006;Jackson, 2007Jackson, , 2008. Although advanced L2ers comprehend word order alternations and evince on-line sensitivity to morphologically marked word order changes at the end of sentences in self-paced reading experiments, they appear unable to integrate inflection and syntax incrementally when non-canonical orders are signalled by morphological case marking.…”
mentioning
confidence: 95%